Diurnal photoperiods and rhythmicity of the phototropic bending response in hypocotyls of sunflower, Helianthus annuus L. seedlings - Vinterhalter, Dragan; Vinterhalter, Branka (Archives of Biological Sciences, 2021)
Paper description: The effects of diurnal and free-running photoperiods on the main parameters of plant phototropism are examined in sunflower, Helianthus annuus L. cv. Kondi (Syngenta). Regular shifts of light and darkness establish diurnal rhythmicity of the phototropic bending response of sunflower seedlings. Darkness synchronizes and adjusts differences in day length of diurnal photoperiods by regulating the position of the phototropic bending minima during nighttime. Circadian regulation in sunflower shows that in free-running conditions it can be quickly abandoned, which points to a programmable malfunction of circadian regulation. Abstract: Research on phototropic (PT) bending in sunflower (Helianthus annuus L. cv. Kondi (Syngenta)) seedling hypocotyls presented herein focused on a comparison of diurnal and free-running photoperiods with the aim of explaining the development of diurnal rhythmicity. PT bending magnitudes and lag phase duration exhibited strong daily rhythmicity in all diurnal photoperiods, contrasting with the uniform PT bending response to constant light (CL) conditions. Plants had a daytime maximum for PT bending magnitudes in experiments starting around midday and a minimum in the dark period in those starting 4 h after dusk. Plants could compensate for large differences in the daytime duration of diurnal photoperiods. They required the first 4 h of darkness to recover and synchronize the PT bending and to start increasing the magnitudes of PT bending. The daily pattern of lag phase duration changes was similar but inverted, showing that synchronization also occurred during nighttime. Darkness was not required for PT bending under CL conditions, however, during diurnal photoperiods it enabled the establishment of diurnal rhythmicity and synchronized changes in PT bending capacity to occur when needed, providing maximal values at midday and minimal during the nighttime. Under prolonged duration of daytime corresponding to the start of CL condition, plantlets rapidly abandoned circadian regulation, their PT bending response becoming arrhythmic.